Novel approach to treatment of rectal mucosa-associated lymphoid tissue lymphoma. (27th January 2011) - Chahil, Neetu; Bloom, Peter; Tyson, Jeremiah; Jazwari, Saad; Robilotti, James; Gaultieri, Nicholas
Abstract : A 78-year-old Hispanic woman with a medical history of osteoporosis, hyperlipidaemia and dyspepsia presented to a gastrointestinal clinic complaining of a small amount of rectal bleeding following bowel movements for 6 months. Colonoscopy demonstrated a 3×3 cm submucosal rectal mass. Pathological analysis revealed ulcerated colonic mucosa with diffuse proliferation suggestive of a lymphoproliferative process. Immunohistochemistry and flow cytometry of the specimen supported a diagnosis of mucosa-associated lymphoid tissue lymphoma. The patient was treated with amoxicillin, clarithromycin and lansoprazole for 2 weeks. A C-14 urea breath test confirmed eradication of Helicobacter pylori . Repeat colonoscopy showed no regression of the tumour. The patient received external beam radiation treatment. Subsequent positron emission tomography/CT scans demonstrated no evidence of viable tumour tissue and no regional or distant metastasis. Follow-up sigmoidoscopy with biopsy revealed no evidence of lymphoma.